Surgical Management of Tibial Plateau Fractures with Locking Compression Plate - Shrestha, Bipan; Kandel, Prakriti Raj; Shrestha, Kishor Man; Shrestha, Shreshal; Yadav, Rakesh (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Tibial plateau fracture is a common fracture that accounts for 1-2% of all fracture. Various treatment options including proximal tibial plating with locking compression plates are available for the treatment of tibial plateau fracture. This study was done to determine the clinical profile and functional outcome of tibial plateau fracture following locking compression plating. MATERIAL AND METHODS This prospective and observational study was carried out in Orthopedics Department of Universal College of Medical Sciences-Teaching Hospital (UCMS-TH) from December 2018 to July 2020. After Ethical clearance (UCMS/IRC/224/18) from Institutional Review Board (IRB) of UCMS-TH and informed written consent, all patients with tibial plateau fracture (Schatzker II-VI) who fulfilled the inclusion criteria were enrolled in the study and treated with locking compression plate. Post-operatively patients were regularly followed at 6 weeks, 3 months and 6 months for clinical, radiological and functional assessment. Descriptive statistics like frequency, percentage, mean and standard deviation were used to analyze the data. RESULTS In our study of 30 cases, the mean age was 37.77 ±15.65 years. Most of the cases were Schatzker type VI (13 patients) and type II (9 patients). The average duration for fractures union was 23.4 ±2.1 weeks. Superficial wound infection was the common complication seen in five cases. At six months, the mean knee society score (KSS) was 78 ±7.22 and majority of patients (19 patients) had good results. CONCLUSION Locking compression plate has an excellent functional and radiological outcome. It is an effective implant that can be adopted for the treatment of tibial plateau fractures in adults.